The Application of the Strict Liability Principle in the Protection of Consumers of Digital Logistics Services: Penerapan Prinsip Strict Liability Dalam Perlindungan Konsumen Jasa Logistik Digital - Diana, Diana; Lie, Gunardi (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The advancement of digital technology has revolutionized the logistics sector through application-based services that offer efficiency and convenience for consumers. Specific background: Nevertheless, the increasing reliance on digital logistics services has created new legal vulnerabilities, particularly when losses are caused by the actions of courier partners as third parties. Knowledge gap: Indonesia still lacks clear regulations governing the application of strict liability within digital logistics services, resulting in uncertainty regarding which party is legally responsible for consumer losses. Aims: This study aims to analyze the application of the strict liability principle in consumer protection within digital logistics services by examining the legal foundations, contractual structures, and implications of liability between companies and their courier partners. Results: The findings show that although the Consumer Protection Law requires business actors to bear consumer losses without proof of fault, its implementation remains weak due to standard contractual clauses that waive company responsibility, low consumer awareness, and limited government oversight. Novelty: This study provides a comprehensive understanding of the multilayered legal relationships between companies, partners, and consumers, highlighting the need for a vicarious liability approach within digital ecosystems. Implications: Strengthening the application of strict liability is essential to ensure fair compensation, increase public trust, and enhance accountability within Indonesia’s digital logistics services. Highlights: Strict liability strengthens consumer protection in digital logistics services. Legal ambiguity persists due to weak regulation and unclear contractual clauses. Companies remain the primary responsible party despite third-party courier involvement. Keywords: Strict Liability, Consumer Protection, Digital Logistics, Legal Responsibility, Courier Partners